Sentiment and dividend smoothing: Do firms alter dividends during periods of high market activity? - Palas, M. Jahir Uddin; Ahmed, M. Adnan (Economics and Business Review, 2025)
This study investigates whether investor sentiment shapes dividend policy among publicly listed firms in Bangladesh by testing the hypothesis that firms alter their dividend smoothing practices in response to market optimism. We utilise a balanced panel of 116 firms from 2010 to 2021, applying robust panel regression techniques, including random effects, panel-corrected standard errors, and instrumental variable estimation to address model imperfections and potential endogeneity. Our findings show that, on average, firms increase dividends during periods of heightened investor optimism. However, this effect is moderated by prior dividend levels, indicating a tendency toward dividend smoothing. Firms appear to balance market sentiment with the need to maintain consistent payout signals. The findings contribute to the behavioural finance literature by highlighting sentiment as a key determinant of dividend behaviour within the Bangladesh context, where market volatility and retail participation are pronounced.